Phosphorylation and Promising In-Vitro Antimicrobial Activity of Some New Organosulfur Compounds - El-Sawi, Emtithal A.; Hosny, Mona A.; El-Sayed, Taghreed H. (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
During the past few decades, interest has been rapidly growing in gaining insight into the properties and transformations of thiosemicarbazide and their derivatives due to their appreciable pharmacological activities. Dimethoxy acetophenone reacts with thiosemicarbazide to afford compound (1). The product allowed to react by fusion with diethylmalonate and ethylacetoacetate to give cyclic compounds (3), (4) and (7). Their products are reacted with triphenylphosphine oxide to produce phosphorylated compounds with four and six membered rings. Some of these products display interesting biological and antibacterial activities which lead to great interest for possible therapeutic uses. The structure of the products are confirmed by elemental analyses, IR, UV, 1H-NMR and MS specra.Â 